Freedom of information in Malaysia: the shade of secrecy / Muhammad Izwan Ikhsan - Ikhsan, Muhammad Izwan (2016)
The notion of freedom of information (FOI) as a universally desired human right is not new. International and regional human rights instruments have recognised the right and many countries all around the globe have FOI laws at the national level. However, after more than half of century of its independence, Malaysia has no specific federal legislation on FOI. Lately, a mounting demand has been made for more openness and transparency in the government sector. This study therefore intends to provide a foundation for FOI law in Malaysia by analysing the approach taken in the United Kingdom and other selected jurisdictions and their compatibility with the existing Malaysian legal framework.